Diagnosis of the Application of NTC ISO 9001: 2015 IN SMEs of the Leather, Footwear and Leather Goods Industry - Ibarguen Rengifo, Aury Janeth; Vargas Hernández, César Asdraldo (Ingeniería Solidaria, 2020)
Introduction: The article is the product of the research "Application of the ISO 9001 standard version 2015 in the leather, footwear and leather goods industry of the Restrepo sector, Bogotá D.C." developed at the Francisco José de Caldas district university during the years 2018 and 2019.Objective: Formulate strategies that allow SMEs to apply ISO 9001: 2015 in the leather, footwear and leather goods industry in SMEs of the Restrepo sector of the city of Bogotá-Colombia.Methodology: Surveys and a bibliographic inquiry were carried out to characterize the subject of the study; make a comparison at an international, national and local level; make a diagnosis of the application of the standard, and propose strategies for its implementation.Conclusion: About 78% of companies in the sector have the potential to be certified in the norm, although they must urgently implement information and communication technologies at the operational and documentary level, and those that are not legally formalized must register before the competent legal entities.Originality: Through this research, strategies for the implementation of ISO 9001: 2015 for SMEs in the Restrepo sector in Bogotá are formulated for the first time.Limitations: The results expose the problems found in a Bogotá cluster, which allow for making inferences for the case of Colombia, but it might not be the case for other countries with higher production or different conditions in the industry.